2003
DOI: 10.1016/s1388-9842(03)00044-8
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the beta‐1 adrenergic receptor Arg389Gly polymorphism in individuals with heart failure: a MERIT‐HF sub‐study

Abstract: Background: The Glycine389 variant of the beta-1 adrenergic receptor (b1AR) generates markedly less cAMP when stimulated in vitro than the more prevalent Arginine389 variant. Aims: The aim of this MERIT-HF sub-study was to ascertain whether this Glycine389 variant favourably influences outcome in heart failure similar to that observed with beta-blockers. Methods: We identified the genotype at amino acid 389 of the b1AR in 600 patients enrolled in the MERIT-HF study (UK and Dutch participants). A risk-ratio (RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
4
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(85 citation statements)
references
References 26 publications
(27 reference statements)
6
74
4
1
Order By: Relevance
“…67 A DNA bank was also established in MERIT-HF, and DNA from 600 patients was analyzed. 165 When outcomes for metoprolol CR/XL were examined by ␤ 1 389 Arg/Gly genotypes, there was no evidence of any differentiation of effect for the all-cause mortality/heart failure hospitalization end point; within the metoprolol group, the hazard ratio for ␤ 1 389 Gly carriers versus Arg/Arg was 0.93 (0.62, 0.40; Pϭ0. 74) and in the placebo group, 1.0 (0.61, 1.64; Pϭ0.99).…”
Section: Polymorphic Variation In ␤ 1 -And ␤ 2 -Arsmentioning
confidence: 97%
See 1 more Smart Citation
“…67 A DNA bank was also established in MERIT-HF, and DNA from 600 patients was analyzed. 165 When outcomes for metoprolol CR/XL were examined by ␤ 1 389 Arg/Gly genotypes, there was no evidence of any differentiation of effect for the all-cause mortality/heart failure hospitalization end point; within the metoprolol group, the hazard ratio for ␤ 1 389 Gly carriers versus Arg/Arg was 0.93 (0.62, 0.40; Pϭ0. 74) and in the placebo group, 1.0 (0.61, 1.64; Pϭ0.99).…”
Section: Polymorphic Variation In ␤ 1 -And ␤ 2 -Arsmentioning
confidence: 97%
“…74) and in the placebo group, 1.0 (0.61, 1.64; Pϭ0.99). 165 It could be argued that differences in enrollment criteria between BEST and MERIT-HF may have influenced these results. However, Figure 7B gives results in ␤ 1 389Arg/Gly genotypic subgroups in a cohort of BEST patients who were selected for the MERIT-HF/CIBIS-II enrollment criteria, 86 the same as for the "BCG" group in Figure 5D.…”
Section: Polymorphic Variation In ␤ 1 -And ␤ 2 -Arsmentioning
confidence: 99%
“…However, negative studies, including larger, well-powered investigations, predominate suggesting that rs1801253 cannot reliably predict antihypertensive response, rate control, or heart failure outcomes 11,17,[53][54][55][56][57][58] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…on the inter-individual variability in the risk of all-cause mortality or hospitalization [47]. Sehnert et al also revealed that Arg389Gly did not significantly influence survival in metoprolol-treated or carvedilol-treated HF patients [48].…”
Section: Anti-hf Therapymentioning
confidence: 96%